MENINGKATKAN MOTIVASI BELAJAR DENGAN MENGEMBANGKAN HARAPAN DAN CITA-CITA PARA SISWA DI RUMAH LANGIT, JAKARTA - handayani, penny; Erianti, Dela; Sugito, Irene Betzy; Lumbu, Irene Novalia (Jurnal Bakti Masyarakat Indonesia, 2023)
Rumah Langit is a social community in East Jakarta that provides education for kids from Marginalized people. Inthe application of teaching and learning activities, a phenomenon was found where there is a lack of opportunitiesfor students to explore themselves extensively, which results in them to not having the opportunity to fulfill their fullpotential, hopes, and also dreams that causes them to not have a motivation for studying. Learning motivation isan inner drive within students that pushes them to engage in learning activities and provides direction to theirlearning so that the desired learning goals can be achieved. The lack of motivation causes them to only come toRumah Langit to meet and play with their friends. Students of Rumah Langit also often demonstrate undisciplinedbehavior while in learning. This issue finally causes the learning activities on Rumah Langit to be unconducivethere for the goal of the study is not fulfilled. To address tis problem, a psychoeducational intervention programwas conducted for the students of Rumah Langit, aged 4-16 years old, in two sessions held on May 19th and 24th.The intervention program aims to help the student understand and cultivate their hope, dream, and learningmotivation, as well as familiarize them with the practical application of these elements in their daily lives. To findout the success of the intervention that we did, we conducted a monitoring and evaluation of the students of RumahLangit, the Teacher, and also the Management of Ruma Langit. Monitoring and evaluation are done by a pretest,posttest, a form of evaluation, and also a questionnaire for teacher, management, and parents of students.Keywords: dreams; hopes; learning discipline; learning motivation ABSTRAKRumah Langit adalah sebuah komunitas sosial di Jakarta Timur yang menyediakan rumah belajar bagi anak-anakdari kaum marjinal. Dalam penerapan kegiatan belajar mengajar, ditemukan sebuah fenomena kurangnyakesempatan untuk mengeksplor diri secara luas yang menyebabkan para siswa belum menyadari potensi diri,harapan, dan cita-cita mereka di masa depan sehingga mereka tidak memiliki motivasi belajar. Motivasi belajaradalah dorongan dalam diri siswa yang menggerakannya untuk melakukan kegiatan belajar, serta memberikan arahpada kegiatan belajarnya sehingga tujuan yang dikehendaki oleh subjek belajar itu dapat tercapai. Kurangnyamotivasi belajar menyebabkan mereka datang ke Rumah Langit hanya untuk bertemu dan bermain bersamateman-teman. Siswa Ruma Langit juga sering menunjukkan perilaku tidak disiplin dalam pembelajaran di kelas.Permasalahan tersebut akhirnya membuat suasana pembelajaran seringkali berjalan dengan tidak kondusifsehingga tujuan pembelajaran tidak tercapai. Untuk mengatasinya, dilakukan program intervensi berbentukpsikoedukasi terhadap para siswa Rumah Langit yang memiliki rentang usia 4-16 tahun dalam dua kali pertemuan,yaitu pada tanggal 19 dan 24 Mei. Program intervensi dilakukan agar para siswa memahami dan memiliki harapan,cita-cita, dan motivasi belajar, serta mengetahui penerapannya dalam kehidupan sehari-hari. Untuk mengetahuikeberhasilan dari program intervensi yang dilakukan, dilakukan monitoring dan evaluasi terhadap para siswa,pengajar, pengurus, dan orang tua siswa di Rumah Langit. Monitoring dan evaluasi dilakukan dalam berbagai cara,seperti pretest, posttest, lembar evaluasi siswa, serta form kuesioner evaluasi bagi pengajar, pengurus, dan orangtua siswa.